2017
DOI: 10.1007/s00464-017-5917-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Safety and effectiveness of self-adhesive mesh in laparoscopic ventral hernia repair using transabdominal preperitoneal route

Abstract: The metadata listed the wrong given names and family names. The correct order is: Given Name Family Name

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the existing literature, we found large studies related to the use of self-adhesive meshes in inguinal hernia, but there are not many concerning the use of this mesh in complex incisional and umbilical hernias. In studies related to the use of retromuscular self-adhesive meshes in complex ventral hernia [ 2 ], the recurrence rate was around 0–30%, similar to the one found in surgical reparation with propylene mesh (2.1–24.1%) [ 13 ]. However, none of those studies employed self-adhesive mesh Adhesix ® ( Cousin Biotech Laboratory, 59117 Wervicq South, France ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the existing literature, we found large studies related to the use of self-adhesive meshes in inguinal hernia, but there are not many concerning the use of this mesh in complex incisional and umbilical hernias. In studies related to the use of retromuscular self-adhesive meshes in complex ventral hernia [ 2 ], the recurrence rate was around 0–30%, similar to the one found in surgical reparation with propylene mesh (2.1–24.1%) [ 13 ]. However, none of those studies employed self-adhesive mesh Adhesix ® ( Cousin Biotech Laboratory, 59117 Wervicq South, France ).…”
Section: Discussionmentioning
confidence: 69%
“…The main surgical advantages are the absence of suture fixation–leaving less prosthetic material in the surgical field–and the consequent saving of intraoperative time. This benefit is associated with less chronic panic in available literature [ 2 , 8 , 12 , 13 ]. The rate of SSI in incisional hernia repair has been reported to be 5–5.9% [ 14 , 15 ], regardless of the type of mesh used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be easy to dissect this space [18], if it contains a substantial amount of connective and fatty tissue, but in quite a few patients, the peritoneum is significantly thin, and there are tight adhesions to the posterior rectus sheath. Therefore, several surgeons intended to dissect this plane for placement of the mesh, but in most of their cases, the rectus sheath was opened and the mesh was placed in the retrorectus position [19,20]. Recently, it was shown that a robot-assisted dissection technique may be beneficial [21,22], but in this technique, a transabdominal approach with all its risks is required so far.…”
Section: Discussionmentioning
confidence: 99%
“…The author proves that laparoscopic prosthetic ventral hernioplasty reduces the volume of the wound defect compared to the open method, is important in patients with comorbidities, and is safe, especially when the ePTFE mesh is used. Compared with conventional open hernioplasty, the laparoscopic technique can reduce the patient's hospitalization time, reduce the number of common postoperative complications as well as frequent complications (seroma development, infection), and facilitate a quicker return to routine activities [11,12]. The use of self-adhesive nets during laparoscopic transabdominal preperitoneal approach for small and medium ventral hernias is safe and effective, with low postoperative pain, rapid functional recovery, and high overall satisfaction after surgery without increasing recurrence in the short term [13].…”
Section: Introductionmentioning
confidence: 99%